Direct Chemical Vapor Phase Deposition of Organometal Halide Perovskite Layers. (16th January 2017) - Stümmler, D.; Sanders, S.; Pfeiffer, P.; Weingarten, M.; Vescan, A.; Kalisch, H.
ABSTRACT: Recently, organometal halide perovskite solar cells have passed the threshold of 20 % power conversion efficiency (PCE). While such PCE values of perovskite solar cells are already competitive to those of other photovoltaic technologies, processing of large-area devices is still a challenge. Most of the devices reported in literature are prepared by small-scale solution-based processing techniques (e.g. spin-coating). Perovskite solar cells processed by vacuum thermal evaporation (VTE), which show uniform layers and achieve higher PCE and better reproducibility, have also been presented. Regarding the co-evaporation of the perovskite constituents, this technology suffers from large differences in the thermodynamic characteristics of the two species. While the organic components evaporate instantaneously at room temperature at pressures in the range of 10 −6 hPa, significantly higher temperatures are needed for reasonable deposition rates of the metal halide compound. In addition, hybrid vapor phase deposition techniques have been developed employing a carrier gas to deposit the organic compound on the previously solution-processed metal halide compound. Generally, vapor phase processes have proven to be a desirable choice for industrial large-area production. In this work, we present a setup for the direct chemical vapor phase deposition (CVD) of methylammonium lead iodide (MAPbI3 ) employing nitrogen as carrier gas. X-ray diffraction (XRD) and scanning electron microscopy (SEM) measurements are carried out to investigate the crystal quality and structural properties of the resulting perovskite. By optimizing the deposition parameters, we have produced perovskite films with a deposition rate of 30 nm/h which are comparable to those fabricated by solution processing. Furthermore, the developed CVD process can be easily scaled up to higher deposition rates and larger substrates sizes, thus rendering this technique a promising candidate for manufacturing large-area devices. Moreover, CVD of perovskite solar cells can overcome most of the limitations of liquid processing, e.g. the need for appropriate and orthogonal solvents.